Green, green, it's green they say: a conceptual framework for measuring greenwashing on firm level - Gregor Dorfleitner; Sebastian Utz (Review of Managerial Science, 2023)
This paper proposes a conceptual framework to determine a greenwashing indicator on firm level, based on five pillars of information that capture the key drivers of greenwashing: soft ESG data, textual self-representation, green marketing expenses, green virtue for the apparent green performance, and hard ESG data as a measure of the real green performance. The proposed framework is built on a literature review of greenwashing typology and drivers and can be applied to a broad set of firms at the same time, while most existing approaches are built on a detailed investigation of individual cases. The greenwashing indicator in our framework is based on the difference between real and apparent green performance. This approach allows the implicit calculation of the real green performance using the concept of a firm misconduct factor that helps to identify the greenwashing indicator without knowledge of the real (and often hard to measure) green performance of a firm.
Keywords: G38; 650; Greenwashing; Greenwashing indicator; Firm misconduct; Real green performance; Apparent green performance; ESG